PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PENINGKATAN HASIL BELAJAR PAI SISWA KELAS VII SMP NEGERI 5 PADANGSIDIMPUAN - Bestari Endayana; Magdalena Magdalena (Jurnal Literasiologi, 2022)
This research discussed a view of learning achievement, the use of jigsawtype cooperative learning in Islamic religion lesson. The background of this research was taken from the lowness of students’ learning achievement which is caused of lecturing and discussion method dominance in teaching presented by the teacher. Then, that problem is frequently happened. Thus, the researcher gave them a solution for that case by using jigsaw-type cooperative learning in learning process. By using jigsaw-type cooperative learning, students’ learning achievement was hopefully improved.The purpose of this research was to know whether the use of jigsaw-type cooperative learning could improve learning achievement of grade VII students in Islamic Religion lesson at SMP Negeri 5 Padangsidimpuan. The kind of this research was a classroom action research which used qualitative method. The samples of this research were 31 students taken from class of VII-4. Test became the instrument of data collection for this research and analyzing the data was done by descriptive qualitative way. According to what the researcher done for this research, it was concluded that using jigsaw-type cooperative learning could improve the learning achievement of VII-4 students. This improvement could be found from the results of testing. The result of cycle I was 6619, cycle II was 7048, and cycle III was 8145. After all, all actions done from cycle I until cycle III showed improvements of learning achievement in Islamic Religion lesson.